The doctoral degree and the professional academic identity development of female academics - Schulze, Salome (South African Journal of Higher Education, 2016)
This longitudinal study explored the professional academic identity development of female academics before and after obtaining their doctoral degrees. The aim was to identify areas to target to support the development of robust professional identities of the academics. Using a narrative research approach, two female academics were interviewed repeatedly over a period of three and a half years. This was complemented by e-mail conversations. Symbolic interactionism and self-efficacy theory were utilised as lens to interpret the data. The research offered three key findings. It revealed that obtaining a doctoral degree does not automatically develop the desired professional identity. The study identified five areas to target when supporting female academics in their identity development. Self-efficacy permeated all five areas.